Interdiscursivity in Public Relations Communication: Appropriation of Genre and Genre Resources - Lung, Jane (HERMES - Journal of Language and Communication in Business, 2015)
Undoubtedly, in recent years, the world as a whole, as well as the present world of work, has seen rapid changes which have served to bring about fundamental changes to work practices. Employees and trainers are thus facing greater challenges to achieve the required competency needed in this changing workplace environment. Bhatia (2013) observes that while the analyses of legal discourse have focused largely on ‘discursive practices’, very little effort has been given to studying ‘critical performance’ in professional legal practices, which is distinct from discursive practices. For this reason, this paper aims to show why discursive output has proved insufficient in the dynamic and complex discourse world of the present day workplace, as well as how the application of Critical Genre Analysis (CGA) greatly assists our understanding of it. By using critical genre theory, this paper looks more closely at interdiscursivity in public relations (PR) involving professional communication and how this in turn results in greater understanding of the changing workplace environment of the PR profession and helps individual PR practitioners cope with the challenges that they face. To achieve these aims, this study includes (i) in-depth interviews with public relations practitioners to gain their perceptions of their daily activities and the language and communication skills required by public relations practitioners to improve their effective professional communication, and (ii) critical genre analysis of the production of PR/communication plans, in particular, the Executive Summary and the Situation Analysis Section of the plans, to show the interaction between discursive and professional practices in the “socio-pragmatic space” of public relations contexts and how interdiscursivity is built into PR genres. For example, in order to examine the appropriation of genre and genre resources, it is interesting to consider: (i) in what way the Executive Summary of the PR/communication plans satisfies the requirements of sales promotional materials, and (ii) how in a very subtle manner, promotional elements are incorporated in the Situation Analysis Section, resulting in a mixed and embedded genre and discourse, achieving a mixture of communicative purposes in the communicative context: to report and to recommend communicative actions as well as to achieve ‘private intentions’ within the context of ‘socially recognized communicative purposes’ (Bhatia 2002).